2021
DOI: 10.2196/25866
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for Implementing App-Based Digital Treatments for Drug Use Disorders Into Primary Care: A Qualitative, User-Centered Design Study of Patient Perspectives

Abstract: Background Digital interventions, such as websites and smartphone apps, can be effective in treating drug use disorders (DUDs). However, their implementation in primary care is hindered, in part, by a lack of knowledge on how patients might like these treatments delivered to them. Objective This study aims to increase the understanding of how patients with DUDs prefer to receive app-based treatments to inform the implementation of these treatments in pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 73 publications
(100 reference statements)
0
13
0
Order By: Relevance
“…In addition to designing features that could meet providers’ motivations, special attention should also be given to the implementation of digital therapeutics in health care systems. Prior studies have suggested possible logistical and workflow challenges, such as training providers to use digital apps with patients in clinical visits, creating a workflow to assist patients in enrolling and setting up digital app programs, and designating personnel and time to review patient-generated data from the digital therapeutics [ 44 , 45 ]. These challenges, if not addressed adequately, could heighten the existing burden of providers and lead to low provider engagement.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to designing features that could meet providers’ motivations, special attention should also be given to the implementation of digital therapeutics in health care systems. Prior studies have suggested possible logistical and workflow challenges, such as training providers to use digital apps with patients in clinical visits, creating a workflow to assist patients in enrolling and setting up digital app programs, and designating personnel and time to review patient-generated data from the digital therapeutics [ 44 , 45 ]. These challenges, if not addressed adequately, could heighten the existing burden of providers and lead to low provider engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to piloting, the study required contracting with the vendor, healthcare system approval of the app’s use of monetary incentives, and an extensive information security risk evaluation. Initial workflow design was informed by two user-centered design studies conducted in partnership clinical leaders [ 51 , 87 ]. After the quality improvement pilot, practice facilitation and health coaching were added to the pilot clinics.…”
Section: Methods / Designmentioning
confidence: 99%
“…A second challenge is that patients often need human support to effectively engage in digital therapeutics [ 53 , 54 , 59 62 ]. Successful implementations must provide support to patients to help them engage in use of apps, without overburdening primary care teams [ 51 , 53 , 54 , 59 , 63 ]. Given the known time constraints and competing demands in primary care [ 25 , 64 ], teams may find it infeasible to offer adequate support for engagement in digital therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…We took inspiration from existing literature on qualitative user-centered design studies in the medical domain that aim to enrich the use cases, attitudes, design requirements, and functionalities about patient-facing digital tools [17,24]. We conducted a remote study using Zoom meetings.…”
Section: Methodsmentioning
confidence: 99%